2021
DOI: 10.21273/hortsci16089-21
|View full text |Cite
|
Sign up to set email alerts
|

Cornstarch-based, Biodegradable Superabsorbent Polymer to Improve Water Retention, Reduce Nitrate Leaching, and Result in Improved Tomato Growth and Development

Abstract: In arid and semi-arid climates, water scarcity and nutrient availability are major constraints for food production. Excess fertilization to make up for the limited nutrient availability in dry soils leads to nitrogen runoff and groundwater contamination. Reducing nitrogen leaching into surface water while providing adequate nutrition remains a major challenge. Superabsorbent polymers (SAPs) can reduce water loss and improve nutrient retention and therefore minimize leaching and increase crop yields. SAPs are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…For instance, Nassaj-Bokharaei et al observed a significant decrease in dry weight and fresh weight of tomato plants grown under nonwater stress conditions (soil moisture content 85%) when the amount of added hydrogel increased from 0.3% to 0.6%. A similar conclusion was reached by Kathi et al…”
Section: Environmental Benefits and Risks Of Hydrogelsupporting
confidence: 88%
See 2 more Smart Citations
“…For instance, Nassaj-Bokharaei et al observed a significant decrease in dry weight and fresh weight of tomato plants grown under nonwater stress conditions (soil moisture content 85%) when the amount of added hydrogel increased from 0.3% to 0.6%. A similar conclusion was reached by Kathi et al…”
Section: Environmental Benefits and Risks Of Hydrogelsupporting
confidence: 88%
“…For instance, Nassaj-Bokharaei et al 150 observed a significant decrease in dry weight and fresh weight of tomato plants grown under nonwater stress conditions (soil moisture content 85%) when the amount of added hydrogel increased from 0.3% to 0.6%. A similar conclusion was reached by Kathi et al 131 In addition, the entire life cycle of hydrogels poses certain ecological and environmental risks. 151 For instance, commercially available hydrogels are predominantly synthetic organic polymer hydrogels composed of poly(acrylic acid) and polyacrylamide, with residues of acrylic acid and acrylamide generated during their synthesis being detrimental to aquatic environments and human health, as they are carcinogenic compounds.…”
Section: Environmental Riskssupporting
confidence: 80%
See 1 more Smart Citation
“…This demand for increased productivity without expanding agricultural lands could be achieved with the use of nanotechnology. Nanotechnology can address several agricultural issues such as the controlled release of active compounds (Singh et al, 2021), selective targeting of pests (Hao et al, 2020;Monteiro et al, 2021), efficient delivery of fertilizers (Guilherme et al, 2010;Ekanayake and Godakumbura, 2021), photoprotection of light-sensitive herbicides (Nguyen et al, 2012), and a way to remediate depleted or dry soils (Kathi et al, 2021;Barajas-Ledesma et al, 2022), but have yet to see widespread practical use. The hesitation surrounding nano-enabled agriculture stems from the many "unknowns" concerning nanomaterials in the environment: what is their fate in soil (Singh and Gurjar, 2022)?…”
mentioning
confidence: 99%